2019
DOI: 10.1049/iet-rpg.2018.6098
|View full text |Cite
|
Sign up to set email alerts
|

Generic Type 3 WT models: comparison between IEC and WECC approaches

Abstract: The widespread use of renewable energies around the world has generated the need for new tools and resources to allow them to be properly integrated into current power systems. Power system operators need new dynamic generic models of wind turbines and wind farms adaptable to any vendor topology and which permit transient stability analysis of their networks with the required accuracy. Under this framework, the International Electrotechnical Commission (IEC) and the Western Electricity Coordinating Council (WE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The following practical effects were incorporated to make the simulations as realistic as possible: discrete‐time implementation, high frequency white noise and transducer dc offset in the measured signals, and detailed IGBT power‐electronics converter models. A family of typical GE®turbine characteristics for various wind and generator speeds, including the MPPT trajectory, used for the simulation studies are displayed in Figure 5(B) [40, 41]. The BDFRG wind turbine specifications can be found in Table 1 and its optimised ‘ducted’ rotor design details (Figure 3) in ref.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The following practical effects were incorporated to make the simulations as realistic as possible: discrete‐time implementation, high frequency white noise and transducer dc offset in the measured signals, and detailed IGBT power‐electronics converter models. A family of typical GE®turbine characteristics for various wind and generator speeds, including the MPPT trajectory, used for the simulation studies are displayed in Figure 5(B) [40, 41]. The BDFRG wind turbine specifications can be found in Table 1 and its optimised ‘ducted’ rotor design details (Figure 3) in ref.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…This is because, on the one hand, this model is able to control the voltage during the fault and, on the other hand, IEC Type 3B WT is only used to represent actual WTs equipped with active crowbar protection systems [19]. Figure 1 shows a schematic representation of generic Type 3 WT and its control models [20]: aerodynamic model, representing the wind turbine rotor (WTR) and providing the value of the wind aerodynamic power; two-mass mechanical model, representing both the low and high speed sides of the gear box (GB); generator system, which provides the values of the active and reactive current injected into the grid and represents the doubly-fed asynchronous (or induction) generator (DFAG); pitch control model, which adjusts the position of the WT blades through calculation of their pitch angle; active power control model (P Control Model), the main output of which is the active current command; reactive power control model (Q Control Model), which provides, based on the reactive power reference, the reactive current command; reactive current limitation model (Q Limitation Model), which calculates the maximum and minimum reactive power allowed; and current limitation model, which provides the active and reactive current's limit values. Moreover, the power converter, also shown in Figure 1, consists of the generator side converter (GSC), the direct current link (DCL), the DC capacitor (C), the chopper protection system (CH) and, lastly, the line side converter (LSC).…”
Section: Generic Type 3 Wind Turbine Model Based On Standard Iec 6140mentioning
confidence: 99%
“…Finally, references [23] addressed the validation of wind farm models according to the WECC guidelines. To support this, a more comprehensive literature review of the works addressing the simulation of generic WT simulation models can be found in References [24,25].…”
Section: Wecc Second Generation Of Wind Turbine Models: Typementioning
confidence: 99%